Single-phase LiY(MoO4)2−x(WO4)x:Dy3+, Eu3+ phosphors with white luminescence for white LEDs. (December 2016) - Zhou, Liangjun; Wang, Wenxi; Yu, Sicen; Nan, Bo; Zhu, Yinggang; Shi, Yang; Shi, Haohong; Zhao, Xingzhong; Lu, Zhouguang
Graphical abstract: Highlights: Highly purified single-phase phosphor is prepared at appropriate metal ions/citric acid and calcination temperature. Influences of pH and Mo 6+ /W 6+ on luminescence are systematically investigated. White-emitting LiY(MoO4 )1.2 (WO4 )0.8 :6%Dy 3+, 7%Eu 3+ phosphor is of good responsiveness to NUV. Abstract: Single-phase and Dy 3+ /Eu 3+ co-doped novel phosphor LiY(MoO4 )2−x (WO4 )x :Dy 3+, Eu 3+, emitting white luminescence under near ultraviolet (NUV) light, was prepared through sol-gel method. The preparation and characterization of this phosphor were systematically studied by X-ray diffraction and spectrofluorophotometric measurements. The molar ratio of metal ions and citric acid (Rm/c ) and calcination temperature greatly influenced the phase purity of sample, revealing that the pure phase could be obtained by using Rm/c  = 1:2.5 and calcination temperature = 800 °C. Under NUV excitation, the as-prepared phosphor exhibited the emissions of 485, 572 and 612 nm, which intensities could be affected by the pH and the concentrations of molybdenum and tungsten ions. By doping appropriate concentrations of Dy 3+ and Eu 3+, white light emitting phosphor LiY(MoO4 )1.2 (WO4 )0.8 :6%Dy 3+, 7%Eu 3+ with good responsiveness to NUV light was obtained. The Commission Internationale de L'Eclairage chromaticity coordinates were calculated to be (x = 0.334, y = 0.322), close to the D65 illuminant (x = 0.313, y = 0.329), indicating the potential application for NUV WLEDs.